Potensi Pengembangan Kawasan Agroekowisata di Kecamatan Singkawang Utara Kota Singkawang - Hazriani, Rini (Pedontropika: Jurnal Ilmu Tanah dan Sumber Daya Lahan, 2023)
Agricultural commodities with their diversity and uniqueness of high value and strengthened by the very diverse cultural richness of Singkawang City have a strong attraction as Agro Tourism, all of which have a great opportunity to become a mainstay in the regional economy. The research aims to inventory and identify potential community land resources for the development of Agroecotourism areas. The research method was carried out in 5 stages: preparation, primary and secondary data collection survey, data processing and analysis and presentation of results (reports and maps). The results of measurements of community-owned land coordinated with the Singkawang City BPN, the total area of land that can be developed as an Agroecotourism area is 1,186 ha, soil types (USDA, 1999) namely Aquandic Dystropept, Typic Haplohemist, Thapto-Histic Fluvaquent and Aquic Psamments, physiography of flat plain land - choppy and very low - medium fertility. Analysis of land potential for agroecotourism areas, namely: KHY (142.56 ha) and MDW (1024,064 ha) suitable for food crops, horticulture, plantation/industry and spices/medicine. HJA (19,799 ha), suitable for food crops, horticulture and plantations/industry. Analysis of water quality, it is known that there are several assessment parameters that do not meet standards so that water rehabilitation at the water location is needed to reduce various chemicals and other suspended materials. The natural tourism potential in this area is in the form of the Sanggang River and Air Hitam River as well as forests. The results of a comprehensive study show that the land of the Setapuk Besar sub-district, North Singkawang District is suitable and feasible to be developed as an Agroecotourism area.